Implementation Of Flipbook-Based E-Module In Basic Competence Of Using Pneumatic Measuring Instrument (Universitas Negeri Semarang, 2022)
The development of appropriate learning media basically aims to create learning conditions that enable students to learn actively and fun so that they can achieve optimal learning outcomes. Therefore, the appropriate learning media is needed.The purpose of this study is to determine the impact of the use of flipbook-based e-modules on learning outcomes in the basic competencies of using pneumatic measuring instruments between two groups of students. This study uses research and development approach.The research at the feasibility test stage involved 2 module expert lecturers, 2 material expert lecturers and tenth grade students of the Automotive Light Vehicle Engineering Skills Competence with a total of 70 students as the control class and the experimental class. It is discovered that the application of e-modules using flipbooks is very practical, feasible, and effective to use to improve student learning outcomes, especially the material on the use of pneumatic measuring instrument. Based on these results, it can be concluded that flipbook e-module can be used to improve student learning outcomes in the competency of using pneumatic measuring instrument.